POTENSI FERMENTABILITAS RUMINAL HIJAUAN PAKAN KAMBING - Anggun Novi Barlian; Marry Christiyanto; Eko Pangestu; Limbang Kustiawan Nuswatara (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
The goal of this experiment was to examine the value of ruminal fermentability that is total VFA and total NH3 of forages for goat. The benefits of this research were can help check the ruminal fermentability of forages for goat and help the efficient formulation of feed as seen from VFA and NH3 production carried out in vitro. The research was done in randomized block design (RBD) with 7 types of forages as treatment and 3 rumen groups as replications. Treatment coverage: R1 = Indigofera leaves; R2 = Insulin leaves; R3 = Guava leaves; R4 = Melinjo leaves; R5 = Rambutan Leaves; R6 = Cassava Leaves; R7: Waru leaves. The result showed that production of NH3 in indigofera leaves, insulin leaves, guava leaves, melinjo leaves, cassava leaves, and waru leaves are optimal for rumen microbial protein synthesis. VFA production in indigofera leaves, insulin leaves, guava leaves, melinjo leaves, rambutan leaves, and cassava leaves can fulfill for rumen microbial growth.